Multisite Replication in Second Language Acquisition Research: Attention to Form During Listening and Reading Comprehension. Issue 2 (June 2018) - Morgan‐Short, Kara; Marsden, Emma; Heil, Jeanne; Issa II, Bernard I.; Leow, Ronald P.; Mikhaylova, Anna; Mikołajczak, Sylwia; Moreno, Nina; Slabakova, Roumyana; Szudarski, Paweł
Abstract: We conducted a multisite replication study with aspects of preregistration in order to explore the feasibility of such an approach in second language (L2) research. To this end, we addressed open questions in a line of research that has examined whether having learners attend to form while reading or listening to a L2 passage interferes with comprehension. Our results are consistent with findings from the specific paradigm that we replicated in that no effects on comprehension were detected in analyses conducted over all sites. However, further investigation is warranted due to site‐specific effects and methodological limitations. We found all aspects of the multisite registered replication approach to be useful although the registration component itself appeared to be an especially feasible and valuable first step toward increasing the robustness and generalizability of findings in our field.